Psychological preconditions for the implementation of the police officers` coping behavior in the context of adaptive perfectionism - S. M. Boiko; V. M. Filonenko (Law and Safety)
The results of the study of psychological preconditions for the implementation of the police officers` coping behavior in the context of an adaptive form of perfectionism are presented. Based on the theoretical analysis of scientific developments of domestic and foreign researchers, it is proved that the types of orientations in difficult situations and tendencies in decision-making are psychological prerequisites for coping behavior, the constructiveness of which determines professional efficiency and positive personalization of the police officers. It is stated that one of the personal factors of overcoming behavior in conditions of professional stress, characteristic for the activity of the police officers, is perfectionism, which, on the one hand, is an important condition for the perfect performance of police duties, but on the other hand, causes ambivalent psychological consequences in accordance with its adaptive or maladaptive form of expression.